INVESTIGATION OF THE INTERACTION OF MERCURO-ION WITH THIOUREA (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The interaction of mercuro-ion with thiourea has been studied by means of potentiometric and amperometric titration methods. The molar ratio (1:2) of the reacting components has been determined. The optimal concentrations of the sulfuric and nitric acids have been revealed: correspondingly 0.1–2 M and 0.1–6 M. The combination of the two methods – potentiometric and amperometric, creates a possibility to determine mercuro-ion within wide range of concentrations (5·10-5 – 7·10-2 М).
Keywords: mercuro-ion; thiourea; potentiometric and amperometric titration methods; sulfuric and nitric acids